Synthesis of Cu2CdSnS4 quaternary alloy nanostructures for dengue serotype-2 DNA biosensor applications - Odeh, Ali Omar Ali Abu (Institute of Nano Electronic Engineering, 2017)
The objectives are as follows to improve the optical, structural, morphological and topographical properties of CCTS quaternary alloy nanostructures deposited on p-type silicon substrates using spin coating technique by optimizing the different deposition process parameters such as ultrasonic and annealing temperature for using CCTS in optoelectronics and dengue DNA biosensor applications; to investigate the effect of using different copper concentrations on the optical, structural, morphological and topographical properties of CCTS quaternary alloy nanostructures deposited on p-type silicon substrates using spin coating technique to be used in optoelectronics and dengue DNA biosensor; to evaluate the analysis and characterization studies of the optical, structural, morphological, topographical and electrical properties of CCTS for using the optimized CCTS quaternary alloy nanostructures in Ag-based Interdigitated Electrodes of dengue serotype-2 DNA biosensor.